Examining the influence of impairment type on the development of Paralympic sport athletes - Dehghansai, N.; Allan, V.; Pinder, R. A.; Baker, J. (Adapted Physical Activity Quarterly, 2023)
Research has recently examined the role of impairment onset on athlete development in Paralympic sport; however, less is known on how impairment type can impact athlete sporting pathways. In this study, 187 Australian and Canadian Paralympic sport athletes completed a survey. Participants were divided into the following four groups: impaired muscle power (n = 79); ataxia, athetosis, and hypertonia (n = 44); limb deficiencies (n = 42); and other physical impairments (n = 22). Mechanisms of initiation into Paralympic sport varied between groups with some drawn to sport through friends and/or family (i.e., limb deficiencies and other physical impairments groups) while others through talent search programs (i.e., ataxia, athetosis, and hypertonia group) or health care professionals/rehabilitation centers (i.e., impaired muscle power group). Results revealed no significant differences between groups in the chronological age or absolute years for achieving milestones. However, considering the high variability within the sample, more research is necessary to better understand how athletes with different physical impairments navigate through their sporting careers.